2013
DOI: 10.1002/jmor.20174
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary morphology of the hemolymph vascular system in hermit and king crabs (Crustacea: Decapoda: Anomala)

Abstract: Cover illustration. The morphological transformation of hermit crabs into king crabs represents one of the evolutionary most fascinating scenarios in decapod evolution. It is certainly the most remarkable case of carcinization, or evolutionary shaping into a crab‐like form. In this issue of the Journal of Morphology Keiler and coauthors (pp. 759–778) investigate the hemolymph vascular system and adjacent anatomical structures of several recent hermit crab (Paguridae) and king crab (Lithodidae) species. The cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 0 publications
2
34
0
1
Order By: Relevance
“…A subsequent morphologically-based phylogenetic study by Richter and Scholtz [56] supported this same evolutionary view of pagurid and lithodid evolution. Recently, a study that examines the hemolymph vascular system in hermit and king crabs found close similarities in arterial systems of the dorsal cephalothorax [57]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent morphologically-based phylogenetic study by Richter and Scholtz [56] supported this same evolutionary view of pagurid and lithodid evolution. Recently, a study that examines the hemolymph vascular system in hermit and king crabs found close similarities in arterial systems of the dorsal cephalothorax [57]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing hermit and king crab circulatory systems identified several vascular changes that occurred as the result of carcinization, arguing for more comparative studies that look at morphology (both internal and external) and development [57]. However, only with a clear phylogenetic hypothesis can many of these studies be correctly interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the hemolymph circulatory systems of arthropods, especially of decapods, has been studied in great detail in recent years (e.g., Keiler, Richter, & Wirkner, , ; McGaw & Reiber, ; McGaw & Stillman, ). However, what has actually been studied in detail is the hemolymph vascular system (i.e., the heart and the arteries), only one of the two constituent subsystems of the hemolymph circulatory system (Wirkner et al, ; Wirkner, Tögel, & Pass, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decapods are known to show the highest degree of complexity in vascular systems within Mandibulata (Keiler et al, , ; McGaw & Reiber, ; Wirkner et al, ), which implies that hemolymph flow has to be accurately and precisely maintained in the various body regions. As the vascular system constitutes only half of the circulatory system, it can be assumed that a specialized and defined lacunar system is equally important for maintaining this precision of hemolymph flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that vascular systems in certain arthropod taxa, such as certain Malacostraca (Sandemann, ; McGaw, ; McGaw and Duff, ; Wirkner and Richter, ; Huckstorf and Wirkner, ; Keiler et al, ), certain Chilopoda (Wirkner and Pass, ) and also many Chelicerata (Wirkner and Prendini, ; Klußmann‐Fricke et al, ; Huckstorf et al, ; Göpel and Wirkner, ) are highly complex. In some arachnopulmonate taxa, this level of complexity has been observed, not only in the hemolymph vascular systems (HVS) in general, but especially in the arterial systems of the prosomal ganglion.…”
Section: Introductionmentioning
confidence: 99%